2022
DOI: 10.1177/19458924221086268
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Montelukast and Azelastine add on Therapy in Moderate to Severe Allergic Rhinitis Treatment: A Double-Blind Randomized Clinical Trial

Abstract: Background Allergic Rhinitis (AR) is a prevalent chronic inflammatory nasal condition with significant negative effects on the patients’ quality of life. This study aimed to investigate the efficacy of Montelukast and intranasal antihistamine in combination with intranasal corticosteroid (INCS) in moderate to severe allergic rhinitis on the patients’ quality of life and AR control. Method This double-blind randomized clinical trial study was carried out on 66 moderate to severe AR patients referred to Namazi H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Switching gears to a prospective investigation, we had an excellent study by Esmaeilzdeh et al prospectively identified 66 moderate to severe allergic rhinitis patients and placed them in 3 treatment arms; montelukast and steroid spray, intranasal antihistamine and steroid spray, and intranasal steroid with a placebo tablet. 3 They found that the nasal antihistamine group with steroid spray was the superior outcomes arms in regard to SNOT-22 scores. Conversely, in their investigation, they found montelukast has no improvement over intranasal steroids alone.…”
mentioning
confidence: 99%
“…Switching gears to a prospective investigation, we had an excellent study by Esmaeilzdeh et al prospectively identified 66 moderate to severe allergic rhinitis patients and placed them in 3 treatment arms; montelukast and steroid spray, intranasal antihistamine and steroid spray, and intranasal steroid with a placebo tablet. 3 They found that the nasal antihistamine group with steroid spray was the superior outcomes arms in regard to SNOT-22 scores. Conversely, in their investigation, they found montelukast has no improvement over intranasal steroids alone.…”
mentioning
confidence: 99%